The Parasite - Serres, Michel 1930-2019; Wolfe, Cary (Minnesota University of Minnesota Press, 2007)
Influential philosopher Michel Serress foundational work uses fable to explore how human relations are identical to that of the parasite to the host body. Among Serress arguments is that by being pests, minor groups can become major players in public dialoguecreating diversity and complexity vital to human life and thought.Michel Serres is professor in history of science at the Sorbonne, professor of Romance languages at Stanford University, and author of several books, including Genesis.